The Implementation of the Traditional Cultural Expression (TCE) Protection in Indonesia Based on Article 38 Law Number 28 of 2014 regarding Copyright - Purwandoko, Prasetyo Hadi; Sulistiyono, Adi; Hawin, M. (Indonesian Journal of International Law, 2021)
Indonesia as a multicultural and multi-ethnicity country has a wide Traditional Cultural Expression (TCE) which needs active protection as a cultural heritage from extinction and to provide certain economic benefits. However, a lot of elements are endangered due to the effect of globalization, lack of facilities, appreciation, and comprehension which cause erosion of values, functions, and cultural elements. This research was, therefore, conducted to discuss the implementation of TCE protection in Indonesia based on Article 38 Law Number 28 of 2014 concerning Copyright (Copyright Law 2014). It was concluded that the implementation of TCE protection is through the Draft of Governmental Decree concerning TCE but this draft has not been promulgated.